Potentiodynamic polarization of Mg-0.22ca alloys containing minor element of Aluminium - Shaiful Rizam, Shamsudin; Mohd Nazree, Derman; C.I., Mahdi; Azmi, Kamardin; Abd. Razak, Daud; Mazlee, Mohd Noor; A.M.H., Firdaus; G., Sasirehka (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.